PLGA nanoparticles containing Lingzhi extracts rescue corneal epithelial cells from oxidative damage. (May 2021) - Tsai, I-Lun; Tsai, Ching-Yao; Kuo, Li-Lin; Woung, Lin-Chung; Ku, Ruy-Yu; Cheng, Yung-Hsin
Abstract: Oxidative stress-related ocular surface epithelial damage can be initiated by ambient oxygen, UV radiation, and chemical burns. The oxidative damage to cornea can lead to inflammation and even vision loss. Lingzhi (Ganoderma lucidum) is a Chinese herbal drug and has been shown to prevent chronic diseases in clinical practices and has been proven to possess anti-oxidative and anti-inflammatory properties. In the study, we prepared poly (lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) as a sustained drug release system of Lingzhi (LZH) to improve bioavailability. The particle size of developed NPs containing LZH (LZH-NPs) was 184 nm with narrow size distribution. The results of cellular uptake revealed that using NPs as a drug delivery system could significantly increases the intracellular retention time. The results of the cell viability and chemiluminescence assay revealed that 5 μg/ml of LZH-NPs might be the threshold concentration for cultivation of corneal epithelial cells. After treating LZH-NPs in oxidative damaged cells, the results showed that the inflammation-related gene expression and DNA fragmentation level were both significantly decreased. Post-treatment of LZH-NPs in damaged corneal epithelial cells could increase the cell survival rate. In the rabbit corneal alkali burn model, topical instillation of LZH-NPs could promote corneal wound healing and decrease the inflammation. These results suggest that LZH-NPs may have the potential to treat ocular surface diseases caused by oxidative stress. Highlights: The PLGA nanoparticles containing Lingzhi extracts are developed and characterized. PLGA nanoparticles increase the intracellular retention time. The developed formulation decreases the inflammation and apoptosis levels of cells. The developed formulation rescues the cells from oxidative damage.